2023
DOI: 10.1007/s00417-022-05966-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of peripapillary staphylomas on the vascular and structural characteristics in myopic eyes: a propensity score matching analysis

Abstract: Purpose To apply propensity score matching to evaluate the impact of peripapillary staphylomas (PPS) on vascular and structural characteristics in the myopic eyes. Methods This was a prospective, cross-sectional study. Forty-one control eyes and 41 eyes with PPS were analyzed. The eyes were selected using propensity score matching analysis based on the age and axial length. All subjects underwent ophthalmologic examinations for assessing vessel and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Peripapillary posterior staphyloma (PPS) is one of six types of posterior staphylomas identified in degenerative myopia ( 198 ). Eyes with PPS have an increased macular vessel density in the deep plexus, reduced macular choriocapillaris and radial peripapillary capillary density, and thinner choroids ( 199 ). In addition, a retrospective study also identified reduced choriocapillaris flow and thinner subfoveal choroidal thickness, confirming that eyes with posterior staphyloma have thinner choroids and lower perfusion ( 200 ).…”
Section: Myopia-associated Conditions Showing Vascular Alterationsmentioning
confidence: 99%
“…Peripapillary posterior staphyloma (PPS) is one of six types of posterior staphylomas identified in degenerative myopia ( 198 ). Eyes with PPS have an increased macular vessel density in the deep plexus, reduced macular choriocapillaris and radial peripapillary capillary density, and thinner choroids ( 199 ). In addition, a retrospective study also identified reduced choriocapillaris flow and thinner subfoveal choroidal thickness, confirming that eyes with posterior staphyloma have thinner choroids and lower perfusion ( 200 ).…”
Section: Myopia-associated Conditions Showing Vascular Alterationsmentioning
confidence: 99%